Optimasi Ekstraksi Fenolik Daun Legetan Warak (Adenostemma Lavenia (L.) Kuntze) Berbantu Gelombang Mikro - Muhamad Najibufahmi; Muhammad Walid; Dewi Azizah (Fakultas Farmasi Universitas Setia Budi, 2019)
Legetan warak (Adenostemma lavenia (L.) Kuntze) is a wild plant which has phenolic compounds and widely used as a natural antibacterial ingredient. The purpose of this study is to obtain the optimum condition of solvent concentration, microwave power and extraction time that appropriate with characteristic of phenolic compounds of leaf of Legetan warak. This experimental laboratory study developed a microwave asissted extraction method. The solvent concentrations which were tested are ethanol 50%, 60%, 70%, 80% and 90% in various extraction times, 1 minute, 3 minute, 5 minute and 9 minute. Meanwhile, the microwave powers which were used are 100 watt, 150 watt, 200 watt, 300 watt and 400 watt. The results showed that the optimum condition of microwave asissted extraction process of leaf of the Legetan warak used ethanol 80% as the solvent with the microwave power 200 watt and the extraction time 5 minute.